Biochemical engineering - Katoh, Shigeo (Weinheim Wiley-VCH, 2015)
The central theme of the textbook remains the application of chemical engineering principles to biological processes in general, demonstrating how a chemical engineer would address and solve problems. To create a logical and clear structure, the book is divided into three parts.